STUDI KUALITATIF NILAI-NILAI EKOFEMINIS PADA KOMUNITAS KERAJINAN TENUN DI DESA SUKARARA KECAMATAN JONGGAT, LOMBOK TENGAH - Nur Choerun Nisa (Program Studi Manajemen Lingkungan, 2017)
Indonesia as an archipelago country, has a diversity of ethnic groups each with local knowledge. That is one of the creative culture of the Sasak tribe of Lombok. This craft is one of the results of human creativity to meet the needs of clothing. Sasak tribe who inhabit the island of Lombok, until now still preserving the weaving craft. One of the supporters of weaving sustainability is the availability of natural dyes derived from plants. In this study, data collection was conducted in Sukarara Village, Jonggat Sub-district, Central Lombok District, West Nusa Tenggara Province which is one of the weaving centers in Lombok. The research method is direct observation in field and interview. The results of the research inform the role of women already considered in decision making concerning natural resources.